A hybrid friction nanogenerator
By designing a hybrid friction nanopower sensor, the three-layer friction structure makes the friction layer material have positive and negative polarity, solving the problem of limited polarity of the friction layer in the prior art, and achieving more efficient power conversion and output performance.
Patent Information
- Application Number
- CN201910870161.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-09-16
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing friction nanopower generation equipment is limited in terms of the number of friction layers, specific arrangement mode and overall configuration, and output efficiency and output performance need to be improved, and compatibility with the working environment needs to be improved.
A hybrid friction nanopower generation sensor is designed. By redesigning the basic configuration and working principle, the friction layer material in a single power generation device can have both positive and negative polarities and on-demand conversion at the same time. It adopts a three-layer friction structure, in which the third friction layer can have both positive and negative polarities at the same time in the working state.
It realizes more sensitive conversion of mechanical energy into electrical energy, improves the power generation efficiency and output capability of nanogenerators, has a compact structure, is easy to operate, and has high compatibility.
Smart Images

Figure CN110572073B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field related to nano power generation equipment, and more specifically, relates to a hybrid friction nano generator. Background Art
[0002] With the rapid development of microelectronics and material technology, a large number of new microelectronic devices with multiple functions and high integration are being developed, and they have shown unprecedented application prospects in various fields of people's daily lives. However, the research on power supply systems that match these microelectronic devices is relatively lagging behind. At present, various research on new energy development and reusable renewable energy is in full swing around the world. Therefore, it is extremely important to develop a technology that can convert naturally existing mechanical energy such as motion and vibration into electrical energy.
[0003] In recent years, nanogenerators based on the friction electrostatic effect have developed rapidly, and with their efficient output, simple process, and stable performance, they provide a very promising way to convert mechanical energy into electrical energy to drive electronic devices. A search found that some technical solutions for nanogenerators based on the friction electrostatic effect have been proposed in the prior art. For example, CN201810714708.1 discloses a friction nanogenerator, in which the first to fourth friction layers are coaxially arranged, and the first friction layer is in contact with the second friction layer and the third friction layer is in contact with the fourth friction layer, and friction is generated by relative rotation, so that the generator starts to generate electricity. For another example, CN201510232639.7 discloses a rotary friction nanogenerator, which includes at least one group of first friction units and second friction units, and the third component is respectively in contact with each of the first and second friction units through friction, so that friction charges are generated on the two friction units. In addition, some nanogenerator products that are not in the form of shafts but in the form of stacking are also disclosed in the prior art.
[0004] However, further research shows that the above-mentioned prior art still has the following defects or deficiencies: First, no matter whether the friction power generation device adopts a stacked form or an axial form, the same friction layer can only have one polarity, which leads to great restrictions on the number of friction layers, specific settings and overall configurations; second, the output efficiency and output performance need to be improved, and it is necessary to increase the compatibility with the working environment. Accordingly, the field urgently needs to make further improvements in order to better meet various complex needs in practical applications. Summary of the invention
[0005] In view of the above defects and improvement needs of the prior art, the purpose of the present invention is to provide a hybrid friction nano-power generation sensor, in which the basic configuration and working principle of the friction nano-power generation sensor are redesigned so that a friction layer material in a single power generation device can have both positive and negative polarities and be converted on demand, thereby more sensitively converting the mechanical energy applied to the friction nano-generator into electrical energy compared with existing equipment. At the same time, it also has the advantages of compact structure, easy operation, and can effectively improve the power generation efficiency and output capacity of the nano-generator.
[0006] According to the present invention, a hybrid friction nano-power generation sensor is provided, characterized in that the friction nano-power generation sensor is in a stacked structure as a whole, and includes a first insulating packaging layer, a first grounding shielding layer, a first insulating layer, a first conductive element, a first friction layer, a third friction layer, a second friction layer, a second conductive element, a second insulating layer, a second grounding shielding layer, and a second insulating packaging layer from top to bottom in the height direction, wherein:
[0007] The lower surface of the first friction layer and the upper surface of the second friction layer are used to contact and separate with the corresponding surfaces of the third friction layer during operation, respectively, to generate relative sliding friction and cause the friction area to change, thereby inducing the transfer of surface charges on these friction layers, and flowing to the first and second conductive elements through the guiding circuit to generate a transient circuit, and accordingly outputting an AC pulse electrical signal to the external circuit via these conductive elements.
[0008] As a further preference, the friction electrode sequences of the first, second and third friction layers are different from each other, that is, the degree of attraction to electric charges is ranked differently, and the friction electrode sequence of the third friction layer is between the first friction layer and the second friction layer.
[0009] As a further preference, the lower surface of the first friction layer and / or the upper surface of the second friction layer and / or the upper and lower surfaces of the third friction layer are preferably distributed with microstructures of the micrometer or sub-micrometer order; and these microstructures are preferably selected from nanowires, nanotubes, nanoparticles, nanogrooves, microgrooves, nanocones, microcones, nanospheres or microsphere-like structures.
[0010] As a further preference, the lower surface of the first friction layer and / or the upper surface of the second friction layer and / or the upper and lower surfaces of the third friction layer are preferably dotted with or coated with nanomaterials.
[0011] As a further preference, the lower surface of the first friction layer and / or the upper surface of the second friction layer and / or the upper and lower surfaces of the third friction layer are chemically modified, so that functional groups that are easy to obtain electrons, such as acyl, carboxyl, nitro or sulfonic acid groups, are introduced into the lower surface material of the first friction layer and / or the lower surface of the third friction layer, and / or functional groups that are easy to lose electrons, such as amino, hydroxyl or alkoxy groups, are introduced into the upper surface material of the second friction layer and / or the upper surface material of the third friction layer.
[0012] As a further preferred embodiment, the lower surface of the first friction layer and / or the upper surface of the second friction layer and / or the upper and lower surfaces of the third friction layer are chemically modified, so that negative charges are introduced into the lower surface material of the first friction layer and / or the lower surface of the third friction layer, and / or positive charges are introduced into the upper surface material of the second friction layer and / or the upper surface of the third friction layer. In addition, the chemical modification is achieved by introducing charged groups through chemical bonding.
[0013] As a further preference, the lower surface of the first friction layer and / or the upper surface of the second friction layer and / or the upper and lower surfaces of the third friction layer are preferably further provided with a plurality of friction units discretely arranged in an array, and the arrangement patterns of the friction units on the relatively placed friction layers keep echoing each other, and ensure that during operation, each friction unit on the lower surface of the first friction layer at least contacts with a friction unit portion on the upper surface of the third friction layer, and each friction unit on the upper surface of the second friction layer at least contacts with a friction unit portion on the lower surface of the third friction layer.
[0014] As a further preference, the first and second conductive elements are films or sheets; the first friction layer, the second friction layer, and the third friction layer are preferably films or sheets.
[0015] As further preferred, the first friction layer, the second friction layer, the third friction layer, the first conductive element, and the second conductive element are hard or flexible.
[0016] Preferably, the cross-sections of the first friction layer, the first conductive element, the second conductive element and the second friction layer are preferably semi-elliptical or semi-circular; the cross-section of the third friction layer is preferably rectangular, circular or elliptical; the cross-sections of the insulating packaging layer and the grounding shielding layer are preferably elliptical or circular.
[0017] As a further preferred embodiment, when the hybrid friction nanogenerator is in a non-working state, the lower surface of the first friction layer and the upper surface of the third friction layer are separated, and the upper surface of the second friction layer is separated from the lower surface of the third friction layer; when it is in a working state, the lower surface of the first friction layer and the upper surface of the third friction layer are in contact and relative friction occurs, and the upper surface of the second friction layer and the lower surface of the third friction layer are in contact and relative friction occurs.
[0018] As a further preference, the third friction layer is made of a conductive material, and the conductive material is preferably selected from indium tin oxide, graphene, silver nanowire film, metal, alloy, conductive oxide or conductive polymer; wherein the metal is gold, silver, platinum, palladium, aluminum, nickel, copper, titanium, chromium, tin, iron, manganese, molybdenum, tungsten or vanadium; the alloy is aluminum alloy, titanium alloy, magnesium alloy, beryllium alloy, copper alloy, zinc alloy, manganese alloy, nickel alloy, lead alloy, tin alloy, cadmium alloy, bismuth alloy, indium alloy, gallium alloy, tungsten alloy, molybdenum alloy, niobium alloy or tantalum alloy.
[0019] As further preferred, the lower surface of the first friction layer and the upper surface of the second friction layer are preferably made of insulating material or semiconductor material, wherein the insulating material is selected from aniline formaldehyde resin, polyoxymethylene, ethyl cellulose, polyamide nylon, polyamide nylon, wool and its fabric, silk and its fabric, paper, polyethylene glycol succinate, cellulose, cellulose acetate, polyethylene glycol adipate, polydiallyl phthalate, regenerated cellulose sponge, cotton and its fabric, polyurethane elastomer, styrene-acrylonitrile copolymer, styrene-butadiene copolymer, wood, hard rubber, acetate, rayon, polymethyl methacrylate, polyvinyl alcohol, polyester, polyisobutylene, polyurethane elastic sponge, polyethylene terephthalate, polyvinyl butyral, butadiene-acrylonitrile copolymer, chloroprene rubber, natural rubber, polyacrylonitrile, poly(vinylidene chloride-CO- acrylonitrile), polybisphenol A carbonate, polychloroether, polyvinylidene chloride, poly(2,6-dimethylpolyphenylene oxide), polystyrene, polyethylene, polypropylene, polydiphenylpropane carbonate, polyethylene terephthalate, polyimide, polyvinyl chloride, polydimethylsiloxane, polychlorotrifluoroethylene, polytetrafluoroethylene or parylene; and the semiconductor material is selected from the following undoped materials: silicon, germanium, Group III and Group V compounds, Group II and Group VI compounds, solid solutions composed of Group III-V compounds and Group II-VI compounds, amorphous glass semiconductors and organic semiconductors, wherein the Group III and Group V compounds are selected from gallium arsenide and gallium phosphide; the Group II and Group VI compounds are selected from thionyl sulfide and zinc sulfide; the solid solution composed of Group III-V compounds and Group II-VI compounds is selected from gallium aluminum arsenide and gallium arsenic phosphide.
[0020] As a further preferred embodiment, the lower surface of the first friction layer and the upper surface of the second friction layer are preferably made of non-conductive oxides, semiconductor oxides or complex oxides, including silicon oxide, aluminum oxide, manganese oxide, chromium oxide, iron oxide, titanium oxide, copper oxide, zinc oxide, BiO 2 and Y 2 O 3 .
[0021] As a further preference, the lower surface of the first friction layer and the lower surface of the third friction layer are preferably made of a friction electrode sequence material with negative polarity, selected from polystyrene, polyethylene, polypropylene, polydiphenylpropane carbonate, polyethylene terephthalate, polyimide, polyvinyl chloride, polydimethylsiloxane, polychlorotrifluoroethylene, polytetrafluoroethylene and parylene.
[0022] Preferably, the upper surface of the second friction layer and the upper surface of the third friction layer are preferably a friction electrode sequence material with positive polarity, selected from aniline formaldehyde resin, polyoxymethylene, ethyl cellulose, polyamide nylon, polyamide nylon, wool and its fabrics, silk and its fabrics, paper, polyethylene glycol succinate, cellulose, cellulose acetate, polyethylene glycol adipate, polydiallyl phthalate, regenerated cellulose sponge, cotton and its fabrics, polyurethane elastomer, styrene-acrylonitrile copolymer, styrene-butadiene copolymer, wood, hard rubber, acetate, rayon, polymethyl methacrylate, polyvinyl alcohol, polyester, copper, aluminum, gold, silver, steel and silicon.
[0023] That is, the lower surface of the third friction layer is a friction electrode sequence material with negative polarity relative to the upper surface material of the second friction layer with positive polarity friction electrode sequence, and the upper surface of the third friction layer is a friction electrode sequence material with positive polarity relative to the lower surface material of the first friction layer with negative polarity friction electrode sequence.
[0024] In general, the paper-based flexible touch sensor and the manufacturing method thereof according to the present invention have the following technical advantages compared with the prior art:
[0025] 1. New breakthroughs in structure and principle. The hybrid friction generator of the present invention has three friction layers, and the third friction layer can have both positive and negative polarities in the working state to form an AC pulse signal output between the first conductive element and the second conductive element. Therefore, it is different from the power generation principle of the traditional friction generator and provides a new design idea for the friction generator.
[0026] 2. Better output performance. By physically or chemically modifying the upper surface of the first friction layer and the lower surface of the second friction layer in the generator, introducing nanostructure patterns or coating nanomaterials, etc., the contact charge density generated when the three friction layers of the friction nanogenerator contact and slide relative to each other under the action of external force can be further increased, thereby improving the output capacity of the generator.
[0027] 3. Efficient use of energy. The generator of the present invention does not require large-scale, high-intensity energy input. It only needs the input mechanical energy to drive the relative sliding between the first friction layer, the second friction layer and the third friction layer. Therefore, it can effectively collect mechanical energy of various intensities generated in nature and people's daily life, and convert it into electrical energy to achieve efficient use of energy; moreover, the friction nanogenerator contains multiple power generation units at the same time, which can greatly improve the output power.
[0028] 4. Simple structure, light and portable, and highly compatible. The generator of the present invention does not require components such as magnets, coils, and rotors, has a simple structure, a small size, is easy to manufacture, and has a low cost. It can be installed on various devices that can make the first friction layer, the second friction layer, and the third friction layer slide relative to each other, and does not require a special working environment, so it has high compatibility.
[0029] 5. Less interference from the outside world. The friction generator of the present invention adds a grounding shielding layer. When working, its grounding treatment can effectively shield the interference of external environmental factors, making the output performance of the device more excellent. When the generator is used as a sensor, its sensitivity is higher.
[0030] 6. Wide range of uses. The generator of the present invention can be used not only as a small power source, but also for high-power generation; in addition, the friction nanogenerator of the present invention can provide direct current output through a bridge rectifier circuit for use by devices requiring direct current; furthermore, the generator of the present invention can also be used as a sensor, such as a pressure sensor or a strain sensor used in a seat belt to monitor the driver's driving status in real time. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the overall structure of a hybrid friction nano-power generation sensor according to a preferred embodiment of the present invention;
[0032] Figure 2 It is used for specific explanation Figure 1 A cross-sectional schematic diagram of the working principle of the triboelectric nanoelectric sensor shown in;
[0033] Figure 3 is a schematic structural diagram of a hybrid friction nano-power generation sensor according to another preferred embodiment of the present invention;
[0034] Figure 4 Is for Figure 1 The open circuit voltage output diagram of the triboelectric nanogenerator when cyclically compressed by 2.5 mm is shown in FIG.
[0035] Figure 5 yes Figure 3 The open circuit voltage output diagram of the friction nanogenerator shown in FIG. 1 under cyclic compression and a pressure of 5N;
[0036] Figure 6 It is a schematic diagram for exemplarily showing that the friction nanogenerator of the present invention is used for driving status monitoring on a seat belt after being arrayed. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0038] The present invention provides a simple friction nanogenerator that converts naturally occurring mechanical energy such as motion and vibration into electrical energy, which can provide a matching power source for microelectronic devices or serve as a sensor. The friction nanogenerator of the present invention utilizes the phenomenon of surface charge transfer when materials with different polarities in the friction electrode sequence come into contact, and converts the mechanical energy of external force into electrical energy.
[0039] The "triboelectric sequence" described in the present invention refers to the ordering of materials according to their attraction to electric charges. At the moment when two materials rub against each other, the negative charge on the friction surface is transferred from the surface of the material with a more positive polarity in the triboelectric sequence to the surface of the material with a more negative polarity in the triboelectric sequence. So far, there is no unified theory that can fully explain the mechanism of charge transfer. It is generally believed that this charge transfer is related to the surface work function of the material, and the charge transfer is achieved by the transfer of electrons or ions on the contact surface. It should be noted that the triboelectric sequence is only a statistical result based on experience, that is, the farther the two materials are apart in the sequence, the greater the probability that the positive and negative charges generated after contact are consistent with the sequence, and the actual results are affected by many factors, such as the roughness of the material surface, the ambient humidity, and whether there is relative friction. It should be further explained that the transfer of charge does not require relative friction between the two materials, as long as there is mutual contact.
[0040] The "contact charge" mentioned in the present invention refers to the charge on the surface of two materials with different triboelectric polarities after contact, friction and separation. It is generally believed that the charge is only distributed on the surface of the material, and the maximum distribution depth is about 10 nanometers. It should be noted that the sign of the contact charge is the sign of the net charge, that is, there may be a negative charge accumulation area in a local area on the surface of a material with a positive contact charge, but the sign of the net charge on the entire surface is positive.
[0041] For the convenience of explanation, the following will be combined Figure 1 The typical structure is used to describe the principle of the present invention, the selection principle of each component and the range of materials, but it is obvious that these contents are not limited to Figure 1 The embodiments shown in the figure can be applied to all technical solutions disclosed in the present invention.
[0042] The first typical implementation method:
[0043] Figure 1 It is a typical structure of the hybrid friction nanogenerator of the present invention, including: an insulating packaging layer 10, a grounding shielding layer 20, an insulating layer 30, a first conductive element 401, a first friction layer 501 placed in contact with the lower surface of the first conductive element, a second conductive element 402, a second friction layer 502 placed in contact with the upper surface of the second conductive element, and a third friction layer 60 located between the first friction layer and the second friction layer. The third friction layer 60 is a conductive material, so an insulating layer 30 is added in the middle. When the applied external force causes the lower surface of the first friction layer 501 to rub against the upper surface of the third friction layer 60, and the upper surface of the second friction layer 502 to rub against the lower surface of the third friction layer 60, and causes the friction area relative to the two to change, due to the difference in friction electrode sequence between the material of the first friction layer 501, the material of the second friction layer 502 and the third friction layer 60, an electrical signal can be output to the external circuit through the first conductive element 401 and the second conductive element 402.
[0044] The working principle of the friction nanogenerator of the present invention is shown in Figure 2 .exist Figure 2 (a) to 2(d), by applying pressure to the insulating packaging layer 10, the lower surface of the first friction layer 501 and the upper surface of the third friction layer 60 are subjected to relative sliding friction, and the upper surface of the second friction layer 502 and the lower surface of the third friction layer 60 are subjected to relative sliding friction, and when the friction areas relative to the two change due to the difference in the magnitude and direction of the applied pressure, since there is a difference in the friction electrode sequence between the material of the first friction layer 501, the material of the second friction layer 502 and the third friction layer 60, the friction process triggers the surface charge transfer of the above-mentioned friction layers.
[0045] See also Figure 2 (b) In order to shield the electric field formed by the surface charges generated by friction and remaining in the first friction layer 501 and the second friction layer 502 due to the gradual increase in the contact area of the friction layer region, the free electrons in the second conductive element 402 will flow to the first conductive element 401 through the external circuit, generating an instantaneous current.
[0046] See also Figure 2 (d) When the external force is released or reversed, in order to shield the electric field formed by the surface charges remaining in the first friction layer 501 and the second friction layer 502 due to the gradual reduction of the contact area of the friction layer area, the electrons in the first conductive element 401 flow back to the second conductive element 402, thereby giving a current in the opposite direction.
[0047] The first friction layer 501 and the second friction layer 502 are respectively composed of materials with different triboelectric properties, and the different triboelectric properties mean that the two are in different positions in the triboelectric sequence, so that the two can generate contact charges on the surface during the friction process. Conventional insulating materials and semiconductor materials both have triboelectric properties and can be used as materials for preparing the first friction layer 501 and the second friction layer 502 of the present invention.
[0048] The insulator can be selected from some commonly used organic polymer materials and natural materials, including: aniline formaldehyde resin, polyoxymethylene, ethyl cellulose, polyamide nylon, polyamide nylon, wool and its fabrics, silk and its fabrics, paper, polyethylene glycol succinate, cellulose, cellulose acetate, polyethylene glycol adipate, polydiallyl phthalate, regenerated cellulose sponge, cotton and its fabrics, polyurethane elastomer, styrene-acrylonitrile copolymer, styrene-butadiene copolymer, wood, hard rubber, acetate, rayon, polymethyl methacrylate, polyvinyl alcohol , polyester, polyisobutylene, polyurethane elastic sponge, polyethylene terephthalate, polyvinyl butyral, butadiene-acrylonitrile copolymer, chloroprene rubber, natural rubber, polyacrylonitrile, poly(vinylidene chloride-CO-acrylonitrile), polybisphenol A carbonate, polychloroether, polyvinylidene chloride, poly(2,6-dimethylpolyphenylene oxide), polystyrene, polyethylene, polypropylene, polydiphenylpropane carbonate, polyethylene terephthalate, polyimide, polyvinyl chloride, polydimethylsiloxane, polychlorotrifluoroethylene, polytetrafluoroethylene and parylene.
[0049] Commonly used semiconductor materials are selected from the following non-doped materials: silicon, germanium, III and V group compounds, such as gallium arsenide and gallium phosphide, etc.; II and VI group compounds, such as sulfide and zinc sulfide, etc.; solid solutions composed of III-V group compounds and II-VI group compounds, such as gallium aluminum arsenic and gallium arsenic phosphide, etc.; in addition to the above-mentioned crystalline semiconductors, amorphous glass semiconductors and organic semiconductors can also be selected; non-conductive oxides, semiconductor oxides or complex oxides can also be used as friction layer materials, including silicon oxide, aluminum oxide, manganese oxide, chromium oxide, iron oxide, titanium oxide, copper oxide, zinc oxide, BiO 2 and Y 2 O 3 .
[0050] The thickness of the first friction layer 501 and the second friction layer 502 has no significant effect on the implementation of the present invention, but factors such as the friction layer strength and power generation efficiency need to be comprehensively considered during the setting process. The present invention preferably uses a thin layer with a thickness of 50nm-2cm, preferably 100nm-1cm, more preferably 1um-5mm, and more preferably 10um-2mm. These thicknesses are applicable to all technical solutions in the present invention.
[0051] The third friction layer 60 is made of a conductive material, and its friction series should be between the friction series of the first friction layer 501 and the second friction layer 502. The conductive material includes: indium tin oxide, graphene, silver nanowire film, metal, alloy, conductive oxide or conductive polymer; wherein the metal is gold, silver, platinum, palladium, aluminum, nickel, copper, titanium, chromium, tin, iron, manganese, molybdenum, tungsten or vanadium; the alloy is aluminum alloy, titanium alloy, magnesium alloy, beryllium alloy, copper alloy, zinc alloy, manganese alloy, nickel alloy, lead alloy, tin alloy, cadmium alloy, bismuth alloy, indium alloy, gallium alloy, tungsten alloy, molybdenum alloy, niobium alloy or tantalum alloy.
[0052] The first conductive element 401, the second conductive element 402 and the ground shielding layer 20 only need to have conductive wire properties, and can be selected from indium tin oxide, graphene, silver nanowire film, metal, alloy, conductive oxide or conductive polymer; wherein the metal is gold, silver, platinum, palladium, aluminum, nickel, copper, titanium, chromium, tin, iron, manganese, molybdenum, tungsten or vanadium; the alloy is aluminum alloy, titanium alloy, magnesium alloy, beryllium alloy, copper alloy, zinc alloy, manganese alloy, nickel alloy, lead alloy, tin alloy, cadmium alloy, bismuth alloy, indium alloy, gallium alloy, tungsten alloy, molybdenum alloy, niobium alloy or tantalum alloy.
[0053] The conductive element may be a film, a layer or a plate, with films and layers being preferred.
[0054] The first conductive element 401 and the second conductive element 402 may be connected to the external circuit through a wire or a metal film.
[0055] The present invention does not limit the first friction layer 501 and the second friction layer 502 to be hard materials, and flexible materials can also be selected, because the hardness of the material does not affect the sliding friction effect between the two, and technicians in this field can make a choice according to actual conditions. Moreover, the advantage of the generator made of flexible materials is that the soft and thin friction layer will be deformed when subjected to a slight external force, and this deformation will cause the relative displacement of the two friction layers, thereby outputting electrical signals to the outside through sliding friction. The use of flexible materials makes the nanogenerator of the present invention also have very wide applications in the fields of biology and medicine. During use, ultra-thin, soft, elastic and / or transparent polymer materials can also be used as substrates for packaging to facilitate use and improve strength. Obviously, all structures disclosed in the present invention can be made of corresponding ultra-soft and elastic materials to form flexible nanogenerators, which will not be repeated here, but various designs derived therefrom should be included in the protection scope of this patent.
[0056] Due to space limitations, it is not possible to enumerate all possible materials. Only a few specific materials are listed here for reference. However, it is obvious that these specific materials cannot become limiting factors for the scope of protection of the present invention, because under the inspiration of the invention, technicians in this field can easily select other similar materials based on the triboelectric properties of these materials.
[0057] Experiments have found that the greater the difference in the triboelectric properties between the materials of the friction layer contact surface, the stronger the output electrical signal of the generator. Therefore, appropriate materials can be selected to prepare the friction layers that contact each other according to actual needs. The triboelectric sequence material with negative polarity is preferably selected from polystyrene, polyethylene, polypropylene, polydiphenylpropane carbonate, polyethylene terephthalate, polyimide, polyvinyl chloride, polydimethylsiloxane, polytrifluorochloroethylene, polytetrafluoroethylene and parylene; the triboelectric sequence material with positive polarity is preferably selected from aniline formaldehyde resin, polyoxymethylene, ethyl cellulose, polyamide nylon 11, polyamide nylon 66, wool and its fabrics, silk and its fabrics, paper, polyethylene glycol succinate, cellulose, cellulose acetate, polyethylene glycol adipate, polydiallyl phthalate, regenerated cellulose sponge, cotton and its fabrics, polyurethane elastomer, styrene-acrylonitrile copolymer, styrene-butadiene copolymer, wood, hard rubber, acetate, rayon, polymethyl methacrylate, polyvinyl alcohol, polyester.
[0058] The surfaces of the first friction layer 501 and / or the second friction layer 502 that are in contact with each other may also be chemically modified, which can further increase the amount of charge transfer at the moment of contact, thereby increasing the contact charge density and the output power of the generator. Chemical modification is divided into the following two types:
[0059] One method is to introduce a functional group that is more likely to lose electrons (i.e., a strong electron-donating group) on the surface of the material with positive polarity, or introduce a functional group that is more likely to gain electrons (a strong electron-withdrawing group) on the surface of the material with negative polarity, which can further increase the amount of charge transfer when sliding against each other, thereby increasing the friction charge density and the output power of the generator. Strong electron-donating groups include: amino, hydroxyl, alkoxy, etc.; strong electron-withdrawing groups include: acyl, carboxyl, nitro, sulfonic acid, etc. The introduction of functional groups can be carried out by conventional methods such as plasma surface modification. For example, a mixture of oxygen and nitrogen can be made to generate plasma at a certain power, thereby introducing amino groups on the surface of the friction layer material.
[0060] Another method is to introduce positive charges on the surface of the friction layer material with positive polarity, and introduce negative charges on the surface of the friction layer material with negative polarity. This can be achieved specifically by chemical bonding. For example, tetraethyl orthosilicate (TEOS) can be modified on the surface of the polydimethylsiloxane (PDMS) friction layer by hydrolysis-condensation (sol-gel) to make it negatively charged. Gold nanoparticles containing hexadecyltrimethylammonium bromide (CTAB) on the surface can also be modified by gold-sulfur bonding on the metal gold film layer. Since hexadecyltrimethylammonium bromide is a cation, the entire friction layer will become positively charged. Those skilled in the art can select suitable modified materials to bond with the friction layer material according to the properties of gain and loss of electrons and the types of surface chemical bonds to achieve the purpose of the present invention, so such deformations are within the scope of protection of the present invention.
[0061] The second typical implementation method:
[0062] Figure 3Another typical structure of the hybrid friction nanogenerator of the present invention includes: insulating packaging layers 101 and 102, grounding shielding layers 201 and 202, insulating layers 301 and 302, gaskets 701-704, a first conductive element 401, a first friction layer 501 placed in contact with the lower surface of the first conductive element, a second conductive element 402, a second friction layer 502 placed in contact with the upper surface of the second conductive element, and a third friction layer 60 located between the first friction layer and the second friction layer. The third friction layer 60 is a non-conductive material. When pressure is applied to the insulating packaging layer, the lower surface of the first friction layer 501 and the upper surface of the third friction layer 60 will be relatively rubbed, and the upper surface of the second friction layer 502 and the lower surface of the third friction layer 60 will be relatively rubbed, and when the friction area relative to the two changes, due to the difference in friction electrode sequence between the material of the first friction layer 501, the material of the second friction layer 502 and the third friction layer 60, the electrical signal can be output to the external circuit through the first conductive element 401 and the second conductive element 402.
[0063] This implementation method and Figure 1 The embodiment shown has the same structure, except that the third friction layer 60 in this embodiment is made of non-conductive material, and no insulating layer is required to separate it; the upper and lower insulating packaging layers, the grounding shielding layer, and the insulating layer are separated rather than integrated; in order to ensure that the friction layers are separated from each other in the initial state (without external force), gaskets 701-704 are added between the friction layers. Figure 2 In addition, the cross-sectional view of the entire device changes from an ellipse to a rectangle.
[0064] The materials of the gaskets 701 - 704 are preferably conventional insulating materials and semiconductor materials.
[0065] The insulator can be selected from some commonly used organic polymer materials and natural materials, including: aniline formaldehyde resin, polyoxymethylene, ethyl cellulose, polyamide nylon 11, polyamide nylon 66, wool and its fabrics, silk and its fabrics, paper, polyethylene glycol succinate, cellulose, cellulose acetate, polyethylene glycol adipate, polydiallyl phthalate, regenerated cellulose sponge, cotton and its fabrics, polyurethane elastomer, styrene-acrylonitrile copolymer, styrene-butadiene copolymer, wood, hard rubber, acetate, rayon, polymethyl methacrylate, polyethylene enol, polyester, polyisobutylene, polyurethane elastic sponge, polyethylene terephthalate, polyvinyl butyral, butadiene-acrylonitrile copolymer, chloroprene rubber, natural rubber, polyacrylonitrile, poly(vinylidene chloride-CO-acrylonitrile), polybisphenol A carbonate, polychloroether, polyvinylidene chloride, poly(2,6-dimethylpolyphenylene oxide), polystyrene, polyethylene, polypropylene, polydiphenylpropane carbonate, polyethylene terephthalate, polyimide, polyvinyl chloride, polydimethylsiloxane, polychlorotrifluoroethylene, polytetrafluoroethylene and parylene;
[0066] Commonly used semiconductor materials are selected from the following non-doped materials: silicon, germanium, III and V group compounds, such as gallium arsenide and gallium phosphide, etc.; II and VI group compounds, such as sulfide and zinc sulfide, etc.; solid solutions composed of III-V group compounds and II-VI group compounds, such as gallium aluminum arsenic and gallium arsenic phosphide, etc.; in addition to the above-mentioned crystalline semiconductors, amorphous glass semiconductors and organic semiconductors can also be selected; non-conductive oxides, semiconductor oxides or complex oxides can also be used as friction layer materials, including silicon oxide, aluminum oxide, manganese oxide, chromium oxide, iron oxide, titanium oxide, copper oxide, zinc oxide, BiO 2 and Y 2 O 3 ;
[0067] The thickness of the gaskets 701-704 plays the role of isolating the friction layer and should be selected according to the structure and size of the device. The preferred thickness of the present invention is 0.5mm-2cm, preferably 1mm-5mm, which is applicable to all technical solutions of the present invention.
[0068] The width of the gaskets 701 - 704 should be smaller than the width of each friction layer to ensure that each friction layer can have partial areas contacting each other and generating friction when subjected to external force.
[0069] In the process of continuous contact and separation of the first friction layer 501, the second friction layer 502 and the third friction layer 60 by applying external force, the first conductive element 401 and the second conductive element 402 connected to the external circuit will output an alternating AC pulse electrical signal with alternating directions to the external circuit, thereby realizing the conversion of mechanical energy into electrical energy.
[0070] Embodiment 1:
[0071] This embodiment uses Figure 1 The friction nano generator configuration shown. The insulating packaging layer 10 is made of a polyethylene terephthalate (PET) film with a thickness of 3um and a size of 13mm×26mm, the ground shielding layer 20 is made of a copper film with a thickness of 5um and a size of 13mm×26mm, the insulating layer 30 is made of a polyimide (PI) film with a thickness of 3um and a size of 13mm×26mm, the first conductive element 401 is made of a copper foil with a thickness of 5um and a size of 12.5mm×12.5mm, the first friction layer 501 is made of a polytetrafluoroethylene (PTFE) film with a thickness of 1um and a size of 12mm×12mm, the second conductive element is made of a copper film with a thickness of 5um and a size of 12.5mm×12.5mm, the second friction layer 502 is made of a letter paper with a thickness of 2um and a size of 12mm×12mm, and the third friction layer 60 is made of an aluminum foil with a thickness of 1um and a size of 10mm×10mm. In the initial state (without external force), the maximum distance between the first friction layer PTFE and the second friction layer paper and the third friction layer is 3 mm. In addition, the surface of the first friction layer PTFE is treated by conductive coupled plasma etching (ICP) to form a nanocolumn array.
[0072] After the wires are led out from the metal copper foils of the first conductive element and the second conductive element, the acrylic sheet is controlled by a linear motor to reciprocately compress the device's insulating packaging layer PET, and when the maximum compression of the device as a whole is 2.5 mm, the lower surface of the first friction layer PTFE and the upper surface of the third friction layer aluminum foil are relatively rubbed, and the upper surface of the second friction layer paper and the lower surface of the third friction layer aluminum foil are relatively rubbed, and the friction area changes periodically, thereby promoting the operation of the friction nanogenerator. The generated open circuit voltage output diagram is shown in FIG. Figure 4 .
[0073] Embodiment 2:
[0074] This embodiment uses Figure 3 The friction nano generator configuration shown. The material type and thickness selection of each layer in this embodiment are basically the same as those in Example 1, with the only difference being that the second friction layer 502 uses a polyamide (PA) film with a thickness of 2um, and the third friction layer 60 uses a polyethylene terephthalate (PET) film with a thickness of 3um. The dimensions of the gaskets 701-704 are 1cm×1cm×6mm, and the length and width dimensions of the remaining layers are 1cm×1cm. In the initial state (without external force), the spacing between the first friction layer PTFE and the second friction layer PA and the third friction layer is 6mm. In addition, the surface of the first friction layer PTFE is treated with conductive coupled plasma etching (ICP) to form a nanocolumn array.
[0075] After the wires are led out from the metal copper foils of the first conductive element and the second conductive element, the acrylic sheet is controlled by a linear motor to reciprocately compress the device insulation packaging layer, and when the maximum pressure on the device as a whole is 5N, the lower surface of the first friction layer PTFE and the upper surface of the third friction layer PET are in relative friction, and the upper surface of the second friction layer polyamide film and the lower surface of the third friction layer PET are in relative friction, and the friction area changes periodically, thereby promoting the operation of the friction nanogenerator. The open circuit voltage output diagram is shown in FIG. Figure 5 .
[0076] The friction nanogenerator of the present invention can use translational kinetic energy to generate electrical energy for small electrical appliances without the need for power supplies such as batteries, and is a convenient generator. In addition, since many movements in nature and human life can generate friction, the power generation method and the nanogenerator and generator set based on the independent friction layer provided by the present invention can be used to collect mechanical energy in many living environments, such as people walking, vehicles traveling, etc. The preparation method of the friction nanogenerator of the present invention is simple and the preparation cost is low, and it is a friction nanogenerator with a wide range of applications.
[0077] The friction nanogenerator of the present invention can also be used as a sensor, for example, to measure the mass of an object, stress, strain, etc. It can also be used to monitor the driving posture of the driver. The friction generator in Example 1 is arrayed and placed on the seat belt. The specific placement position is as follows: Figure 6 As shown, during driving, due to different actions and postures of the driver, the seat belt intermittently contacts the shoulders and waist of the human body and the contact area changes, the lower surface of the first friction layer PTFE and the upper surface of the third friction layer aluminum foil are relatively rubbed, and the upper surface of the second friction layer paper and the lower surface of the third friction layer aluminum foil are relatively rubbed. The first conductive element and the second conductive element are connected through electrode wires to form a path, generate voltage and current, and draw a voltage distribution diagram of the sensor during driving. The driver's driving action can be judged according to the difference in voltage size and frequency, thereby evaluating the driver's irregular driving state.
[0078] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A hybrid friction nano-power generation sensor, characterized in that: The friction nano power generation sensor has a stacked structure as a whole, and comprises, from top to bottom along the height direction, a first insulating packaging layer (10), a first grounding shielding layer (20), a first insulating layer (30), a first conductive element (401), a first friction layer (501), a third friction layer (60), a second friction layer (502), a second conductive element (402), a second insulating layer (30′), a second grounding shielding layer (20′), and a second insulating packaging layer (10′), wherein: The lower surface of the first friction layer (501) and the upper surface of the second friction layer (502) are used to contact and separate from the corresponding surface of the third friction layer (60) during operation, thereby generating relative sliding friction and causing the friction area to change, thereby inducing surface charge transfer on these friction layers, and flowing to the first and second conductive elements through the guiding circuit to generate a transient circuit, and correspondingly outputting an AC pulse electrical signal to an external circuit via these conductive elements; There are differences between the friction electrode sequences of the first, second and third friction layers, that is, the degree of attraction of electric charges is ranked differently, and the friction electrode sequence of the third friction layer is between the first friction layer and the second friction layer; the lower surface of the first friction layer and the lower surface of the third friction layer are friction electrode sequence materials with negative polarity, and the upper surface of the second friction layer and the upper surface of the third friction layer are friction electrode sequence materials with positive polarity.
2. A hybrid friction nano-power generation sensor as claimed in claim 1, characterized in that: The surface of the first friction layer and / or the second friction layer is preferably also distributed with micron or sub-micron microstructures, and these microstructures are selected from nanowires, nanotubes, nanoparticles, nanogrooves, microgrooves, nanocones, microcones, nanospheres and microspherical structures.
3. A hybrid friction nano-power generation sensor as claimed in claim 1 or 2, characterized in that: The surface of the first friction layer and / or the second friction layer is preferably provided with a plurality of friction units arranged in a discrete array, and the arrangement patterns of the friction units on the first and second friction layers placed opposite to each other are kept in correspondence, and it is ensured that during operation, each friction unit on the surface of the first friction layer is in partial contact with at least one friction unit on the surface of the second friction layer.
4. A hybrid friction nano-power generation sensor as claimed in claim 1, characterized in that: The cross-sections of the first friction layer, the first conductive element, the second conductive element and the second friction layer are preferably semi-elliptical or semi-circular; the cross-section of the third friction layer is preferably rectangular, circular or elliptical; the cross-sections of the insulating packaging layer and the grounding shielding layer are preferably elliptical or circular.
5. A hybrid friction nano-power generation sensor as claimed in claim 1, characterized in that: When the hybrid friction nano-power generation sensor is in a non-working state, the lower surface of the first friction layer is separated from the upper surface of the third friction layer, and the upper surface of the second friction layer is separated from the lower surface of the third friction layer; In the working state, the lower surface of the first friction layer contacts and generates relative friction with the upper surface of the third friction layer, and the upper surface of the second friction layer contacts and generates relative friction with the lower surface of the third friction layer.
6. The hybrid friction nano-power generation sensor according to claim 1, characterized in that: The lower surface of the first friction layer and the upper surface of the second friction layer are preferably made of insulating material or semiconductor material, wherein the insulating material is selected from aniline formaldehyde resin, polyoxymethylene, ethyl cellulose, polyamide nylon, polyamide nylon, wool and its fabric, silk and its fabric, paper, polyethylene glycol succinate, cellulose, cellulose acetate, polyethylene glycol adipate, polydiallyl phthalate, regenerated cellulose sponge, cotton and its fabric, polyurethane elastomer, styrene-acrylonitrile copolymer, styrene-butadiene copolymer, wood, hard rubber, acetate, rayon, polymethyl methacrylate, polyvinyl alcohol, polyester, polyisobutylene, polyurethane elastic sponge, polyethylene terephthalate, polyvinyl butyral, butadiene-acrylonitrile copolymer, chloroprene rubber, natural rubber, polyacrylonitrile, poly(vinylidene chloride-CO-acrylonitrile) , polybisphenol A carbonate, polychloroether, polyvinylidene chloride, poly(2,6-dimethylpolyphenylene oxide), polystyrene, polyethylene, polypropylene, polydiphenylpropane carbonate, polyethylene terephthalate, polyimide, polyvinyl chloride, polydimethylsiloxane, polychlorotrifluoroethylene, polytetrafluoroethylene or parylene; and the semiconductor material is selected from the following undoped materials: silicon, germanium, Group III and Group V compounds, Group II and Group VI compounds, solid solutions composed of Group III-V compounds and Group II-VI compounds, amorphous glass semiconductors and organic semiconductors, wherein the Group III and Group V compounds are selected from gallium arsenide and gallium phosphide; the Group II and Group VI compounds are selected from thionyl sulfide and zinc sulfide; the solid solution composed of Group III-V compounds and Group II-VI compounds is selected from gallium aluminum arsenide and gallium arsenic phosphide.
7. The hybrid friction nano-power generation sensor according to claim 1, characterized in that: The lower surface of the first friction layer and the upper surface of the second friction layer are made of non-conductive oxides, semiconductor oxides or complex oxides, including silicon oxide, aluminum oxide, manganese oxide, chromium oxide, iron oxide, titanium oxide, copper oxide, zinc oxide, BiO2 and Y2O3.
8. The hybrid friction nano-power generation sensor according to claim 6 or 7, characterized in that: The third friction layer is made of a conductive material, and the conductive material is preferably selected from indium tin oxide, graphene, silver nanowire film, metal, alloy, conductive oxide or conductive polymer; wherein the metal is gold, silver, platinum, palladium, aluminum, nickel, copper, titanium, chromium, tin, iron, manganese, molybdenum, tungsten or vanadium; the alloy is aluminum alloy, titanium alloy, magnesium alloy, beryllium alloy, copper alloy, zinc alloy, manganese alloy, nickel alloy, lead alloy, tin alloy, cadmium alloy, bismuth alloy, indium alloy, gallium alloy, tungsten alloy, molybdenum alloy, niobium alloy or tantalum alloy.
9. The hybrid friction nano-power generation sensor according to claim 6 or 7, characterized in that: The lower surface of the first friction layer and the lower surface of the third friction layer are selected from polystyrene, polyethylene, polypropylene, polydiphenylpropane carbonate, polyethylene terephthalate, polyimide, polyvinyl chloride, polydimethylsiloxane, polytrifluorochloroethylene, polytetrafluoroethylene and parylene; correspondingly, the upper surface of the second friction layer and the upper surface of the third friction layer are selected from aniline formaldehyde resin, polyoxymethylene, ethyl cellulose, polyamide nylon, polyamide nylon, wool and its fabrics, silk and its fabrics, paper, polyethylene glycol succinate, cellulose, cellulose acetate, polyethylene glycol adipate, polydiallyl phthalate, regenerated cellulose sponge, cotton and its fabrics, polyurethane elastomer, styrene-acrylonitrile copolymer, styrene-butadiene copolymer, wood, hard rubber, acetate, rayon, polymethyl methacrylate, polyvinyl alcohol, polyester, copper, aluminum, gold, silver, steel and silicon.
Citation Information
Patent Citations
A rotating triboelectric nanogenerator
CN106208801B
Friction nano-generator
CN110165928A
Sliding friction nano generator and power generation method
CN103354429A
Wind power generation and solar power generation combining system adopting nanometer friction generators
CN104113270A
Micro-vibration sensor
CN104953888A